Intention to trust on purchasing online food services among millennials / Muhammad Sirajuddin Wahab - Wahab, Muhammad Sirajuddin (Faculty of Business and Management, 2019)
The main objective of this project paper was conducted to identify the intention to trust on purchasing online food services among millennials. This study also indicates the relationship between independent variables (integrity, benevolence, competency, firm’s image and price awareness) and dependent variable (intention to trust on purchasing online food services). This research is quantitative research and the survey were collected on 141 on numbers of respondent through questionnaire. The data has been analysed and evidences are being processed by using SPSS software. Based on the findings, the result shows that, the hypothesis testing display only integrity and price awareness are accepted, while the other three hypotheses concerning benevolence, competency and firm’s image are rejected. In conclusion, it shows that with good integrity and showing the price will increase the intention to trust to online food services vendors.